Red state religion: faith and politics in America's heartland - Wuthnow, Robert (Princeton University Press, 2012)
Piety on the plains. Abraham Lincoln in Kansas. Establishing a civic order. Public religion. Serving the community. Church expansion. Cooperation and competition -- An evolving political style. Prairie politics. Populism and religious politics. Protesting against inequality. A divided party. Law and order. For the children -- Redefining the heartland. Harvest of progress. Consolidation and expansion. Forward-looking initiatives. Church and state. Hunkering down. Fundamentalism and the Great Depression. Simian peasants. Novel movements -- Quiet conservatism. Grassroots resentments verso the Senator from Pendergast. Hometown religion. I like Ike. A well-qualified Catholic -- An era of restructuring. Stirrings on the right. From desegregation to Black Power. Nixon at Kansas State. Division in the churches -- The religious right. Mobilization on the right. Government is the problem. The war in Wichita. Shifting the focus. Questioning evolution -- Continuing the struggle. The churches and activist networks. Electing George W. Bush. Regulating abortion. The campaign against gay marriage. Evolution revisited. The death of Dr. Tiller. Swatches of purple